Exploring Deep Reinforcement Learning for Battling in Collectible Card Games - Vieira, Ronaldo; Tavares, Anderson; Chaimowicz, Luiz (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2022: Anais do XXI Simpósio Brasileiro de Jogos e Entretenimento Digital, 2022)
Collectible card games (CCGs), such as Magic: the Gathering and Hearthstone, are a challenging domain where game-playing AI arguably has not yet reached human-level performance. We propose a deep reinforcement learning approach to battling in CCGs, using Legends of Code and Magic, a CCG designed for AI research, as a testbed. To do so, we formulate the battles as a Markov decision process, train agents to solve it, and evaluate them against two existing agents of different skill levels. Contrasting with the current state-of-the-art, our resulting agents act fast and can play many battles per second, despite their limited performance. We identify limitations and discuss several promising directions for improvement.